PENGARUH VALUE ADDED CAPITAL EMPLOYED (VACA), VALUE ADDED HUMAN CAPITAL (VAHU), STRUCTURAL CAPITAL VALUE ADDED (STVA)TERHADAP PROFITABILITAS - Hj. Dewi Rejeki, SE., Ak., M.Si., CA.; Luthfiyah Salsabila (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2021)
This research was conducted on Metal Sub-Sector Manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the 2015-2019 period. The method of determining the sample using purposive sampling method with the sample used 11 companies. Technical analysis of the data used is descriptive statistics and multiple linear regression analysis using SPSS version 22. The results showed that partially Value Added Capital Employed (VACA) and Value Added Human Capital (VAHU) had a significant effect on Profitability and Structural Capital Value Added (STVA) had no significant effect onPprofitability. Then Value Added Capital Employed (VACA), Value Added Human Capital (VAHU) and Structural Capital Value Added (STVA) simultaneously have a significant effect on Profitability